The Impact of Decentralization Dimensions on Subsidiaries Performance - Ahmad Saleem Tarwneh (International Review of Management and Marketing, 2019)
The main objective of this study is to examine the impact of the decentralization dimensions represented in (goals congruence, autonomy and information asymmetry) on subsidiaries performance. The results have showed that there is a statistically significant impact for both goals congruence and autonomy on subsidiaries performance, whereas there is no statistically significant impact for information asymmetry on subsidiaries performance. In the light of the results, some conclusions were drawn, most importantly is that the increased awareness of the managers in subsidiaries by creating a kind of consistency or integration between objectives. Autonomy is an important factor that influences on performance, pointing to the degree of managers' freedom in making managerial decisions. The exchange of information between the subsidiaries within the same group is not considered as a basic requirement for disclosure. Based on conclusions, the study recommends to increase coordination between the objectives of the Organization to create a kind of partnership in achieving the objectives, increase the degree of freedom of management at the lower levels in decision-making, and focus on the quality of information disclosure within the organization.